2019
DOI: 10.1021/acs.jmedchem.8b01615
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Transient Receptor Potential Vanilloid 4 (TRPV4) Agonists as Regulators of Chondrogenic Differentiation: Identification of Quinazolin-4(3H)-ones and in Vivo Studies on a Surgically Induced Rat Model of Osteoarthritis

Abstract: Osteoarthritis (OA) is a degenerative disease characterized by joint destruction and loss of cartilage. There are many unmet needs in the treatment of OA and there are few promising candidates for disease-modifying OA drugs, particularly, anabolic agents. Here, we describe the identification of novel quinazolin-4­(3H)-one derivatives, which stimulate chondrocyte cartilage matrix production via TRPV4 and mitigate damaged articular cartilage. We successfully identified the water-soluble, highly potent quinazolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…We could not find any direct thermo and/or mechano-biological study in the literature reporting even partial effect of TRPV4 blocking on Sox9 expression in chondrogenic cells. However, in agreement with our findings, in vivo and in vitro studies have shown that pharmacological activation/inhibition of TRPV4 channels could mediate Sox9 expression [31,48].…”
Section: Calcium Signaling Is a Major Mechanism Of Action In Transduction Of Thermomechanical Cues Sensed By Trpv4 Channelssupporting
confidence: 93%
See 2 more Smart Citations
“…We could not find any direct thermo and/or mechano-biological study in the literature reporting even partial effect of TRPV4 blocking on Sox9 expression in chondrogenic cells. However, in agreement with our findings, in vivo and in vitro studies have shown that pharmacological activation/inhibition of TRPV4 channels could mediate Sox9 expression [31,48].…”
Section: Calcium Signaling Is a Major Mechanism Of Action In Transduction Of Thermomechanical Cues Sensed By Trpv4 Channelssupporting
confidence: 93%
“…TRPV4 activity can modulate intracellular calcium transients and literature findings indicate that a welladjusted TRPV4-mediated Ca 2+ signaling is necessary for correct biological functioning of chondrocytes [5,[29][30][31][32]. We found that full removal of external calcium sources could further diminish the enhanced chondrogenic response obtained by thermo-mechanical cues when compared with TRPV4 inhibition alone.…”
Section: Calcium Signaling Is a Major Mechanism Of Action In Transduction Of Thermomechanical Cues Sensed By Trpv4 Channelsmentioning
confidence: 65%
See 1 more Smart Citation
“…Most effective is the synthetic lipid GSK1016790A [59,60], which also requires the distant part of the amino-terminus of the channel suggesting a similar activation mechanism as for cell swelling [37]. Recently, local application of quinazolin-4(3 H)-one derivatives as TRPV4 agonists to joint cartilage stimulated chondrocyte matrix production and provided relieve from osteoarthritic damage in a rat model [61].…”
Section: Figure 1 (A)mentioning
confidence: 99%
“…Additionally, stimulation of TRPV4 reduces inflammation by inhibiting interleukin-1β mediated cartilage degradation (Fu et al, 2021). Pharmacological agonism of the TRPV4 channel has also shown therapeutic promise in promoting chondrogenic differentiation and inhibiting cartilage degradation during post-traumatic OA (Atobe et al, 2019). These studies underscore TRPV4 as a regulator of chondrocyte mechanotransduction and as a viable therapeutic target for treating OA.…”
Section: Introductionmentioning
confidence: 98%